Desempenho de híbridos de milho de alto e médio potencial produtivo - Santos, Carlos Eduardo Weber dos (2010)
This study analyzed the positioning of hybrid corn seed company Biomatrix being analyzed for agronomic characteristics, ie its production capacity respectively. We analyzed the following cities: Carazinho, RS, Coxilha, RS, Ponta Grossa, PR and Xanxerê, SC. Data were subjected to analysis of variance (ANAVA) using the significance levels of 5% for the test F. We used the multiple comparison test of Tukey, to assess differences between treatment means when the F value was significant. Statistical analyzes were performed using the statistical package CoStat. The results were not statistically different, because the weather behaved so heterogeneous in the duration of the work, however hybrids and BMX828 BMX817 of high and medium potential yield respectively, expressed relative yield greater witness, remaining always in the top group in productivity.